2021
DOI: 10.1101/2021.03.09.21253179
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prediction of COVID-19 mortality among hospitalized patients in Sudan

Abstract: Background: COVID-19 was primarily reported in China. The mortality rate across countries had ranged from 1% up to more than 10% and it is underestimated in some countries. Advanced age is the most frequently reported factor associated to mortality. Other factors were the presence of comorbidities such as diabetes mellitus, hypertension and obesity. Several models for mortality prediction had been developed to assist in improving the prognosis. The aim of our study was to assess the factors related to mortalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The sample sizes of verified COVID-19 patients ranged from 105 to 2617. The prevalence of diabetes mellitus among the patients in the studies ranged from 6% to 49% [12][13][14][15][16][17][18]. The available meta-analysis on the association of diabetes mellitus and mortality risk with COVID-19 reported ORs ranging from 1.75 to 9.9.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…The sample sizes of verified COVID-19 patients ranged from 105 to 2617. The prevalence of diabetes mellitus among the patients in the studies ranged from 6% to 49% [12][13][14][15][16][17][18]. The available meta-analysis on the association of diabetes mellitus and mortality risk with COVID-19 reported ORs ranging from 1.75 to 9.9.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…Several observational studies on predictors of mortality in COVID-19 patients have been undertaken in Africa, with mixed results regarding the role of diabetes as a comorbidity in death. Diabetes has been demonstrated to be a predictor of mortality in some studies [ 12 - 14 ], although this idea has not been supported in others [ 15 - 18 ]. Varied study designs and populations provide different estimates and impact sizes in these published publications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some African studies have found hypertension to be a predictor of mortality, [14][15][16] while others have not. [17][18][19][20][21] These studies had different study designs and study populations and have therefore produced different estimates and effect sizes. Consequently, a comprehensive and systematic analysis was needed to minimize such variability.…”
mentioning
confidence: 99%